PENGEMBANGAN DAN PENGUKURAN APLIKASI PENYULUHAN PENYAKIT TUBERKULOSIS PARU TERHADAP PENGETAHUAN SERTA SIKAP PENGAWAS MINUM OBAT (Jurnal Kesehatan Siliwangi, 2021)
The background of this research is the high pulmonary tuberculosis in the city of Bandung of 11,959 cases. One of the countermeasures for pulmonary tuberculosis is the direct supervision strategy of swallowing drugs by a drug-taking supervisor. There needs to be a tool to facilitate the role of drug-taking supervisors containing health messages about pulmonary tuberculosis. The purpose of this study was to determine the development and influence of an Android-based mobile application in counseling pulmonary tuberculosis on the knowledge and attitudes of drug-taking supervisors. The research design used is the Research & Development (R&D) design which begins with a needs assessment, media validation, media testing, and measuring the effect on the knowledge and attitudes of drug-taking supervisors. The results of the assessment of media experts and material experts on this assessment were categorized as "Very Eligible". In addition, in this study, there was an increase in knowledge and changes in attitudes from supervisors of taking pulmonary tuberculosis drugs.